BACTERIAL CONTAMINATION AND ANTIBIOTIC RESIDUE ON PORK IN WET MARKETS IN ABIANSEMAL AND KUTA DISTRICTS IN BADUNG REGENCY - Arthawan, I Made; Mahatmi, Hapsari; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2021)
This study aimed to determine the bacterial contamination and antibiotic residues on pork and provided an overview of the handling conditions of pork sold in wet markets in the Abiansemal and Kuta, Badung traditional markets. This study was a cross-sectional study using questionnaires and testing bacterial contamination and antibiotic residues in pork. Questionnaires and pork samples were collected from 26 pork sellers from 8 wet markets, then the data were discussed descriptively. Bacterial contamination tests were carried out by calculating the value of Total Plate Count, Coliform , Escherichia coli , Salmonella sp , Staphylococcus aureus , and Campylobacter sp . The antibiotic residue test was carried out by a screening method (bioassay) against tetracycline and penicillin antibiotics. The results showed that the mean total plate count was 3,7 x 10 5 (7,3 x 10 3 to 1,5 x 10 6 colonies/gram).  The contamination of Coliform and Escherichia coli were 1,3 x 10 5 dan 2,1 x 10 4 respectively with (1,1 x 10 3 to 4,4 x 10 5 colonies/gram) and (4,5 x 10 1 to 9,7 x 10 4 colonies/gram). Contamination of Staphylococcus aureus was the negative results up to 2 x 10 1 colonies/gram. Contaminations of Salmonella sp and Campylobacter sp were negative. Tetracycline and penicillin antibiotic residues were found in 15.38% and 11.54% of all pork samples. The level of public understanding and awareness of the handling and sanitation of pork was found in 50% of respondents who were in the adequate category and 50% in the categories lacked understanding and were less aware of sanitation. Factors that influence the level of bacterial contamination were hygiene practices and sanitation practices of pork sellers 7.7% in the good category, 80.8% in the moderate category and 11.5% in the low category. In conclusion, pork in the traditional markets of Abiansemal and Kuta in Badung Regency is contaminated with bacteria and contains antibiotic residues, and from the aspect of veterinary public health, it was not suitable for consumption.